From Ruling Party to Opposition Party: The People’s Democratic Party in Nigeria’s 2015 General Elections (Journal of Governance and Development (JGD), 2023)
The objective of this paper is to examine the factors that led to the defeat ofthe Peoples Democratic Party (PDP) in Nigeria’s 2015 general electionsafter dominating Nigeria’s political landscape since the return to democracyin 1999.The methodology of the paper is qualitative and conceptual. The issueswere analysed under various themes. The data were gathered through thesecondary method of data collection such as textbooks, journal articles,reports of election observer teams, party constitutions, workshop papers,Independent National Electoral Commission (INEC) documents, theElectoral Acts and the 1999 Constitution of the Federal Republic of Nigeria.The analysis of the information gathered helped to dissect the circumstancesthat were responsible for the electoral defeat of the Peoples DemocraticParty (PDP) by the current ruling All Progressives Congress (APC) in the2015 general elections.The research discovered that some factors were responsible for the defeatof the PDP in the 2015 general elections, chief among them is the abysmallack of internal party democracy in the party. The paper asserts that thoughpolitical parties are indispensable institutions in a democracy, for themto make fundamental contributions to democracy, they must, among otherthings, adhere to the tenets of internal party democracy in order to sustaintheir electoral strength and make a profound contribution to democraticgrowth.